1957
DOI: 10.3181/00379727-94-22885
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Corticoid Activities of 6-Methyl- 1-Hydrocortisone

Abstract: 159absence of exogenous sources of fluid, Na and C1, supports the view that one of the functions of the adrenal cortex is the regulatory control of the internal distribution of water and certain electrolytes between body compartments. The mechanism of action of the cortical steroids in effecting these changes remains an unsolved problem. Summary.2-methyl-9~-fluorohydrocortisone will revive adrenalectomized dogs from severe insufficiency and restore them to normal health within 48-60 hours even though they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1957
1957
1964
1964

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…FROM SYSTEMIC THERAPY The results reported from long-term therapy with cortisone or hydrocortisone show considerable variation. Some investigators have estimated that not more than 25 per cent of rheumatoid patients may be controlled successfully for 2 years or longer, but most have found that adequate improvement may be maintained in one half or more of their patients6 The disparity is accounted for, in part, by dissimilarities in the composition of the various series in respect to disease severity, by divergences in schemes of dosage, and by differences in judgment as to the degree of induced hyperadrenal manifestations that can be tolerated safely.…”
Section: Cortisone and Hydrocortisone : Over-all Resultsmentioning
confidence: 99%
“…FROM SYSTEMIC THERAPY The results reported from long-term therapy with cortisone or hydrocortisone show considerable variation. Some investigators have estimated that not more than 25 per cent of rheumatoid patients may be controlled successfully for 2 years or longer, but most have found that adequate improvement may be maintained in one half or more of their patients6 The disparity is accounted for, in part, by dissimilarities in the composition of the various series in respect to disease severity, by divergences in schemes of dosage, and by differences in judgment as to the degree of induced hyperadrenal manifestations that can be tolerated safely.…”
Section: Cortisone and Hydrocortisone : Over-all Resultsmentioning
confidence: 99%
“…(2) Corish, P. J., Chapman, D., J . Chern Spectrophotometric Deter mi nation of Resid u a I ECENTLY, A114-3-ketosteroids, such R as prednisolone and 60-methylprednisolone, have assumed commercial importance because of their high glucocorticoid and anti-inflammatory activities (1, 6,8,11). Their production involves chemical (5) or microbiological ( 7 ) dehydrogenation of appropriate A4-3-ketosteroids and a method for the determination of residual A4-3-ketosteroids in A1,4-3-ketosteroids is needed.…”
Section: Acknowledgmentmentioning
confidence: 99%
“…The nitration procedure described was suggested by the qualitative method in the British User's Memorandum (6) and by the A S T X method (1). Materials most likely to cause erroneous results may be removed by extraction, and those that remain uneatracted (carbon black, fillers, and other polymers) interfere slightly, if a t all.…”
Section: Thioseinicarbazidementioning
confidence: 99%
“…These methylated compounds owe their potency to the likely possibility that they are only slowly metaboF.Led in the body. Finally, the analogue I-dehydro-6-methyl-hydrocortisone, is a glucocorticoid which pro motes excretion rather than retention of salt and water (379).…”
Section: Aoren Al Cortexmentioning
confidence: 99%